2016
DOI: 10.3892/etm.2016.3916
|View full text |Cite
|
Sign up to set email alerts
|

Long-term nicotine exposure induces dysfunction of mouse endothelial progenitor cells

Abstract: Endothelial progenitor cells (EPCs) have an important role in maintaining endothelial homeostasis. Previous studies reported that smoking has detrimental effects on EPCs; however, recent studies revealed that short-term nicotine exposure may benefit EPCs. As most smokers are exposed to nicotine over an extended time period, the present study aimed to investigate the long-term effects of nicotine on EPCs. Mice were administered nicotine orally for 1, 3 or 6 months. The mice exposed to nicotine for 1 month demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 36 publications
3
11
0
Order By: Relevance
“…Other CVR factors did not show any impact on colony formation or circulating EPCs, neither if compared to the controls nor if exclusively analyzed between axSpA patients. These data are not truly surprising since comparable observations have been made in the past, at least in hypertension and nicotine abuse [35, 36]. Statins have been documented to increase peripheral EPCs [37].…”
Section: Discussionsupporting
confidence: 66%
“…Other CVR factors did not show any impact on colony formation or circulating EPCs, neither if compared to the controls nor if exclusively analyzed between axSpA patients. These data are not truly surprising since comparable observations have been made in the past, at least in hypertension and nicotine abuse [35, 36]. Statins have been documented to increase peripheral EPCs [37].…”
Section: Discussionsupporting
confidence: 66%
“…On the other hand, the second statement, i.e., “prolonged exposure to nicotine resulted in decreased EPC number,” is an affirmation that smoking is injurious to health. As a result, the above study [172] underscores the cessation of smoking to prevent endothelial dysregulation.…”
Section: Current Prospectsmentioning
confidence: 98%
“…It was hypothesized that the increased EPC activity was due to the antiapoptotic effect of nicotine on EPCs via activation of the nicotinic acetylcholine receptor (nAChR) [170]. However, in another study, it was postulated that nicotine activates telomerase activity through either the PI3K/AKT pathway (by increased phosphorylation of human telomerase reverse transcriptase (hTERT) [171, 172] or upregulation of sirtuin type 1 (SIRT1) protein expression [172]. Telomerase activity may be responsible for cellular senescence [173].…”
Section: Current Prospectsmentioning
confidence: 99%
See 1 more Smart Citation
“…As discussed before, the main trigger for EPC mobilization is the endothelial expulsion of VEGF-2 and SDF-1 -two cytokines responsible for the homing of EPCs to the vascular wall [114]. Li et al demonstrated in mice that daily oral administration of nicotine caused an initial increase of EPC proliferation in vitro following one month of exposure and then a subsequent decrease of EPC proliferation at both, 3 and 6 months [170]. In addition, they also showed that these EPCs showed signs of dysfunction.…”
Section: Endothelial Progenitor Cellsmentioning
confidence: 99%